1969
DOI: 10.2466/pms.1969.28.3.927
|View full text |Cite
|
Sign up to set email alerts
|

Hypnotizability, Laterality of Eye-Movements and Functional Brain Asymmetry

Abstract: The direction of lateral eye-movements upon inward direction of attention or reflection is related to hypnotic susceptibility. A predominance of left eye-movements is associated with greater hypnotizability and also with humanistic interests, relatively poorer mathematical performance on the Scholastic Aptitude Test, and clearer imagery. Results are discussed in terms of functional asymmetry of the brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
98
0
4

Year Published

1974
1974
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 336 publications
(103 citation statements)
references
References 16 publications
1
98
0
4
Order By: Relevance
“…CLEMs refer to the eye movements people make as they begin to think about something. It has been hypothesized that the predominance of CLEMs in one direction is indicative of higher activation in the contralateral hemisphere [53]. For example, people with predominant left CLEMs, or ‘left movers’, are considered to have a dominant RH.…”
Section: Behavioral Studies Of the Rh Deficit Modelmentioning
confidence: 99%
“…CLEMs refer to the eye movements people make as they begin to think about something. It has been hypothesized that the predominance of CLEMs in one direction is indicative of higher activation in the contralateral hemisphere [53]. For example, people with predominant left CLEMs, or ‘left movers’, are considered to have a dominant RH.…”
Section: Behavioral Studies Of the Rh Deficit Modelmentioning
confidence: 99%
“…According to this method, individuals showing a predominance of left CLEMs (left movers) during ongoing cognitive processing are assumed to rely more on their right cerebral hemisphere, while those showing a predominance of right CLEMs (right movers) are thought to rely more on their left hemisphere [31,32], Con trary to the prediction that alexithymia would be associated with a predominance of right eye movements (indicating left cerebral later alization), Cole and Bakan [30] found that left movers were more alexithymic in a sample of 102 right-handed college students. In an at tempt to explain this apparent paradox, these researchers suggested that alexithymia might be associated with an overactivation of the right hemisphere, resulting in a disruption of certain mechanisms involved in the process ing of emotions.…”
mentioning
confidence: 99%
“…During thepast decade, CLEM thus emerged as one of the main indices of hemisphericity (e.g., Bakan, 1969;Breitling & Bonnet, 1985;Cole & Bakan, 1986;Griffiths & Woodman, 1985;Lenhart & Katkin, 1986), although certain writers (e.g., Beaumont , 1983;Beaumont, Young , & McManus, 1984;Ehrlichman & Weinberger, 1978) have criticized such usage. A number of studies, usually using right-handed subjects, claim that CLEM predominates to the right when the content of the questions is verbal and to the left when the content is spatial (e.g.…”
Section: A Harvey Baker Queens College Of the City University Of Newmentioning
confidence: 99%
“…Male left-movers are better at a task involving detection of their own heartbeats (Hantas, Katkin, & Reed, 1984) . Male left-movers are more susceptible to hypnosis (Bakan, 1969;Bakan & Svorad, 1969; R. C. Gur & R. E. Gur, 1974;Morgan, McDonald, & MacDonald, 1971).…”
Section: A Harvey Baker Queens College Of the City University Of Newmentioning
confidence: 99%
See 1 more Smart Citation